Inside Cover: Design and Fabrication of a Tip‐Like ZnO Nanotube Array Structure with Condensate Microdrop Self‐Propelling Function (ChemNanoMat 11/2016). Issue 11 (11th October 2016) - Luo, Yuting; Gong, Xiaojing; Chen, Ying; Zhu, Jie; Wei, Jiandong; Gao, Xuefeng
Abstract : A new type of tip‐like nanotube array with condensate microdrop self‐propelling (CMDSP) function has been designed and fabricated. Based on the basic principle that condensate microdrops can self‐remove via coalescence‐released weak surface energy as long as interface adhesion induced energy dissipation is sufficiently low, tip‐like nanotubes with extremely low solid‐liquid interface adhesion were designed. To verify the feasibility of this idea, preferential etching of six corners and inner of ZnO nanopencils was used to achieve tip‐like nanotubes. After silane modification, this nanostructure showed CMDSP function. This work offers a new avenue for developing CMDSP functional films, which can have a variety of technological applications such as moisture self‐cleaning, antifrosting and enhancing heat transfer. More information can be found in the Communication by X. Gao et al. onpage 1018 in Issue 11, 2016 (DOI:10.1002/cnma.201600207 ).